No Difference in Growth Outcomes up to 24 Months of Age by Duration of Exposure to Maternal Antiretroviral Therapy Among Children Who Are HIV-Exposed and Uninfected in Malawi - Toledo, Gabriela; Landes, Megan; van Lettow, Monique; Tippett Barr, Beth A.; Bailey, Heather; Thorne, Claire; Crichton, Siobhan (Frontiers in Pediatrics, 2022)
Background: With the implementation of lifelong antiretroviral therapy (ART) for HIV treatment and prevention, the proportion of children exposed to ART in utero from conception is increasing. We estimated the effect of timing of ART exposure on growth of children HIV-exposed and uninfected (CHEU) up to age 24 months in Malawi. Methods: Data were collected from a prospective cohort of infants HIV-exposed aged 1-6 months (enrolment) and their mothers with HIV enrolled in the National Evaluation of Malawi’s Prevention of Mother-to-Child Transmission of HIV Programme (2014-2018). Anthropometry was measured at baseline, visit 1 (approx. 12 months), and visit 2 (approx. 24 months). Weight-for-age (WAZ) and length-for-age (LAZ) were calculated using the WHO Growth Standards. Multivariable mixed-effects models with linear splines for age were used to examine differences in growth by timing of ART exposure (from conception, first/second trimester, or third trimester/postpartum). Models were adjusted for confounders selected a priori guided by a Conceptual Framework. Hypothesized interactions and potential mediators were explored and interactions with splines were included in final models if P<0.1. Results: 1,206 singleton CHEU and their mothers enrolled and 563 completed follow-up through age 24 months. 48% of CHEU were exposed to ART from conception, 40% from first/second trimester, and 12% from third trimester/postpartum. At enrolment, 12% infants had low birthweight, 98% had been breastfed in past 7 days, and 57% were enrolled in an HIV Care Clinic. CHEU growth trajectories demonstrated cohort-wide growth faltering after age 12 months. Of 788 and 780 CHEU contributing to WAZ and LAZ multivariable models respectively, there was no evidence of differences in mean WAZ or LAZ among those exposed from conception or first/second trimester vs. third trimester/postpartum and no evidence of a difference in WAZ or LAZ rate of change by timing of ART exposure (all interactions P>1.0). Conclusion: Reassuringly, ART exposure from conception was not associated with decreased WAZ or LAZ in CHEU up to age 24 months. Overall growth trajectories suggest CHEU experience growth faltering after 12 months of age and may need support through and beyond the first two years of life.